History of the Tamiang Pantun Tradition and Its Relevance in History Learning in High Schools - Prasetyo, Okhaifi; Dilwan, Muhammad Al (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
Globalization impacts the younger generation, especially students who do not know the history of their culture. This study aims to reconstruct the history of the pantun reciprocal tradition that lives in the Malay community of Aceh Tamiang and to analyze the relevance in history learning at the high school level. The research method used is descriptive qualitative with observation, interviews, and documentation. The data analysis has three steps: data reduction, data presentation, and conclusion. The study results show that the Tamiang Pantun reciprocal tradition has existed since the 16th century. Starting from scholars and clerics who created prose, poetry, and oral traditions such as pantun and popular poetry, there was a change during the colonial period due to cultural acculturation between Malay and Javanese cultures. Other changes occurred, such as pantun being delivered singly in the past and tended to be monologic. Now, people are developing the Pantun reciprocal tradition as a form of two-way interaction that is more communicative and interesting. The Tamiang Pantun reciprocal tradition is relevant in developing local culture-based history learning. The tradition of responding to pantun in history learning is relevant to phase E (grade X), with the main topic in this phase being the development of Islamic Kingdoms in Indonesia, which includes discussions on the process of Islamization, the role of local figures, and the social and cultural values ​​that developed during that period.